Valentino's syndrome: a bizarre clinical presentation. Issue 2 (6th February 2023) - Machaku, Dennis; Suleman, Mujaheed; Mduma, Elias; Nkoronko, Mugisha
Abstract: A perforated peptic or duodenal ulcer may cause an unusual expression of right lower quadrant pain. In Valentino's syndrome, the chemical fluid from the ulcer flows via the right paracolic gutter to the right iliac fossa, causing peritoneal irritation and chemical appendicitis which will mimic pain in the right lower quadrant. We report a case of a 23-year-old male patient who presented with cramping lower abdominal pain with fevers and vomiting. His pain was mostly in the right lower quadrant and radiated to his back. A perforation-related pneumoperitoneum was found on a computed tomography scan, along with an accumulation of fluid in the abdomen and thickening of the pyloric antrum. Valentino's syndrome's aberrant clinical picture mimicking acute appendicitis is a pathognomonic presentation of the disease. Right lower abdominal pain should also prompt the scrutiny of atypical differentials, such as perforated ulcers. Physicians need to manage these patients with a high index of suspicion.